2007
DOI: 10.1105/tpc.106.047761
|View full text |Cite
|
Sign up to set email alerts
|

ARF7 and ARF19 Regulate Lateral Root Formation via Direct Activation ofLBD/ASLGenes inArabidopsis

Abstract: Lateral root formation in Arabidopsis thaliana is regulated by two related AUXIN RESPONSE FACTORs, ARF7 and ARF19, which are transcriptional activators of early auxin response genes. The arf7 arf19 double knockout mutant is severely impaired in lateral root formation. Target-gene analysis in arf7 arf19 transgenic plants harboring inducible forms of ARF7 and ARF19 revealed that ARF7 and ARF19 directly regulate the auxin-mediated transcription of LATERAL ORGAN BOUNDARIES-DOMAIN16/ASYMMETRIC LEAVES2-LIKE18 (LBD16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
891
2
12

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 880 publications
(946 citation statements)
references
References 64 publications
41
891
2
12
Order By: Relevance
“…To investigate the temporal and spatial expression of LBD genes during callus induction, we chose LBD16 and LBD18 as the representatives and carefully examined their expression patterns during callus induction using ProLBD16:GUS and ProLBD18:EGFP:GUS transgenic seedlings. Consistent with previous observations [27,28,35], LBD16 was only expressed in LRP, root stele nearby LRP and emerged lateral roots ( Figure 2A). However, after seedlings were incubated on CIM for 12 h, GUS staining expanded to the stele of elongation zone in primary roots ( Figure 2B), and subsequently to leaves and the vascular tissues of both roots and hypocotyls after 24 h ( Figure 2C).…”
Section: Lbd16 Lbd17 Lbd18 and Lbd29 Are Dramatically And Rapidly Isupporting
confidence: 80%
See 3 more Smart Citations
“…To investigate the temporal and spatial expression of LBD genes during callus induction, we chose LBD16 and LBD18 as the representatives and carefully examined their expression patterns during callus induction using ProLBD16:GUS and ProLBD18:EGFP:GUS transgenic seedlings. Consistent with previous observations [27,28,35], LBD16 was only expressed in LRP, root stele nearby LRP and emerged lateral roots ( Figure 2A). However, after seedlings were incubated on CIM for 12 h, GUS staining expanded to the stele of elongation zone in primary roots ( Figure 2B), and subsequently to leaves and the vascular tissues of both roots and hypocotyls after 24 h ( Figure 2C).…”
Section: Lbd16 Lbd17 Lbd18 and Lbd29 Are Dramatically And Rapidly Isupporting
confidence: 80%
“…Of the 43 LBD members in the Arabidopsis genome, the expressions of LBD16, LBD17, LBD18 and LBD29 are all inducible by auxin [28,36], a phytohormone required for callus induction in in vitro plant regeneration [15]. More importantly, LBD16, LBD29 and LBD18 have been shown to regulate lateral root formation, a pathway that callus formation may follow [12,14,27,28].…”
Section: Overexpression Of Lbd Genes Is Sufficient To Trigger Callusmentioning
confidence: 99%
See 2 more Smart Citations
“…9 In Arabidopsis, LBD6 functions in the establishment of adaxial-abaxial polarity, 10 LBD30 is involved in embryogenesis, 11 and LBD16, LBD18, LBD29 and LBD33 control lateral root development. [12][13][14] As the Arabidopsis eFP browser showed that LBD10 expression was specifically and strongly increased during pollen development, we conducted functional Keywords: asymmetric cell division, lateral organ boundaries domain, LBD10, LBD27, plant development, pollen development, transcription factor Abbreviations: ASL, asymmetric leaves 2-like; LBD, lateral organ boundaries domain; SCP, sidecar pollen.…”
mentioning
confidence: 99%